A comparison of mechanisms for setting generic drug prices in Canada. (March 2017) - Hollis, Aidan; Grootendorst, Paul
Canadian drug plan pricing of generic drugs is in a state of flux, with different plans adopting different approaches. The manner in which public plans pay for generic drugs can affect five policy goals: low generic drug prices, security of the drug supply, a reliance on reimbursement rules (thereby avoiding the need for drug plan managers to exercise discretion over reimbursement levels), low administrative burden and finally, the provision of adequate incentives for generics to enter the market. We review five pricing mechanisms: maximum prices, tiered pricing, tendering, benchmarking and pharmacy competition. We examine international evidence on the success of the first three of these. We conclude with an assessment of promising reimbursement approaches.